Why is telerehabilitation necessary? A pre-post COVID-19 comparative study of ICF activity and participation. Issue 2 (19th May 2021) - Marotta, Nicola; Demeco, Andrea; Moggio, Lucrezia; Ammendolia, Antonio
Abstract : Purpose: This study aims to evaluate the relevance of telerehabilitation during the spread of the COVID-19 pandemic based on the prevalence of participation and activity International Classification of Functioning, Disability and Health (ICF) domains in a population with disabilities. Design/methodology/approach: We perfomed an observational study of ICF files of people with disabilities pre- and post-three-months lockdown imposed by the government to stop the spread of the COVID-19 pandemic. Findings: ICF qualifiers such as performing the daily routine (d230), using communication devices and techniques (d360) and doing housework (d640) showed a significant decrease of the disabilities (p < 0.05). Instead, a significant increase (p < 0.05) in disability was evident in relating with strangers (d730); informal social relationships (d750); acquiring, keeping and terminating a job (d845); complex economic transactions (d865); community life (d910); and recreation and leisure (d920). Practical implications: Telerehabilitation should not be regarded as home-based rehabilitation delivered through technology. The results show how telerehabilitation should be a functional diagnostic tool and monitoring of patients' rehabilitation needs. Originality/value: Through a comprehensive classification scale of disability, it is possible to redefine the term telerehabilitation.